Xenotransplantation: immunological hurdles and progress toward tolerance. Issue 1 (March 2014) - Griesemer, Adam; Yamada, Kazuhiko; Sykes, Megan
Summary: The discrepancy between organ need and organ availability represents one of the major limitations in the field of transplantation. One possible solution to this problem is xenotransplantation. Research in this field has identified several obstacles that have so far prevented the successful development of clinical xenotransplantation protocols. The main immunologic barriers include strong T‐cell and B‐cell responses to solid organ and cellular xenografts. In addition, components of the innate immune system can mediate xenograft rejection. Here, we review these immunologic and physiologic barriers and describe some of the strategies that we and others have developed to overcome them. We also describe the development of two strategies to induce tolerance across the xenogeneic barrier, namely thymus transplantation and mixed chimerism, from their inception in rodent models through their current progress in preclinical large animal models. We believe that the addition of further beneficial transgenes to Gal knockout swine, combined with new therapies such as Treg administration, will allow for successful clinical application of xenotransplantation.